Implementasi Single Identity Number Kartu Keluarga Berdasarkan Undang-Undang Nomor 24 Tahun 2013 Tentang Administrasi Kependudukan - Fachraini, Raden Shiva Nabila; HB, Gusliana; Akmal, Zainul (Jurnal Ilmiah Wahana Pendidikan, 2024)
Single Identity Number (SIN) is a population identity number that is unique or distinctive, single and attached to someone who is registered as an Indonesian resident. Indonesian citizens and foreigners who have permanent residence permits are only allowed to be registered on one Family Card. This means that a person who is polygamous, even though both marriages are legally valid, cannot be registered on two Family Cards (KK). This is because each resident can only have one Population Identification Number (NIK) which is recorded on one family card (KK). If more than one family card is recorded, it will be recorded as duplicate data. One case of having a SIN occurred in a person named Mr. S. Mr. S had 2 family cards. The reason he has two family cards is because he is polygamous which requires him to be the head of a family who has two wives and two family cards. This research discusses the Single Identity Number in the Family Card to reduce the number of unregistered marriage couples in Pekanbaru City and what factors inhibit the implementation of the Single Identity Number Family Card as well as the efforts made by the Pekanbaru City Government in the Family Card making service.